2003
DOI: 10.1063/1.1538320
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Auger deexcitation and temperature quenching of the Er-related 1.54 μm emission with an ultrathin oxide interlayer in an Er/SiO2/Si structure

Abstract: A strong enhancement of the Er3+-related 1.54 μm emission was obtained from Er-doped porous silicon (PSi), when host PSi was slightly oxidized before Er incorporation. Separate measurements of the energy transfer and the Auger deexcitation between carriers in Si crystallites of preoxidized PSi and Er3+ ions were measured as functions of the preoxidized time or the thickness of the SiO2 interlayer, and revealed that a 1 nm order thick SiO2 interlayer between Si crystallites and Er3+ ions suppressed the Auger en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
5
21
0
Order By: Relevance
“…Yet Er 3+ luminescence from bulk, crystalline Si is known to undergo severe temperature quenching [3]. Thus, we conclude that the Er 3+ ions excited via carriers generated in Si-NWs are actually in the sol-gel derived Er-doped silica film that is coating the Si-NWs, in agreement with previous reports that Er 3+ ions in a nm-thin silica shell around Si have both high carrier-mediated excitation efficiency and high Er 3+ luminescence efficiency irrespective of quantum effects [12]. …”
Section: Discussionsupporting
confidence: 80%
“…Yet Er 3+ luminescence from bulk, crystalline Si is known to undergo severe temperature quenching [3]. Thus, we conclude that the Er 3+ ions excited via carriers generated in Si-NWs are actually in the sol-gel derived Er-doped silica film that is coating the Si-NWs, in agreement with previous reports that Er 3+ ions in a nm-thin silica shell around Si have both high carrier-mediated excitation efficiency and high Er 3+ luminescence efficiency irrespective of quantum effects [12]. …”
Section: Discussionsupporting
confidence: 80%
“…In this case the minimum separation of an Er 3+ ion to the upper surface of a Si NP underneath will be of ϳ1 nm. For Er 3+ in silica-based systems characteristic energy transfer distances from 0.5 to 2-3 nm have been reported, [1][2][3] and therefore for the film with s = 4 nm it is suggested that there is negligible energy transfer from the Si NPs to the Er 3+ layers deposited before the Si NPs, which are at a separation of 4 nm, and that the effective energy transfer is mainly due to the Er 3+ layer deposited after each Si NP layer. From these results it can thus be estimated that there is effective energy transfer from Si NPs to Er 3+ ions in Al 2 O 3 for a distance of ϳ1 nm.…”
Section: Si Np-er Energy Transfer: Critical Distance and Fraction mentioning
confidence: 99%
“…As a result the NPs remain amorphous and the film is not modified by diffusion processes that might modify the original structure, as in most previous reports. [1][2][3]5 This procedure opens a route to the development of one step low-temperature processing for codoped nanostructured waveguide devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations